DOES CORPORATE GOVERNANCE TAKEN SERIOUSLY BY IRAQI LISTED COMPANIES? - Ibrahim Ahmad Anwar (European Scientific Journal, ESJ, 2015)
This research investigates how serious Corporate Governance is taken by listed companies in Iraqi Stock Exchange (ISX), as well as determining the reasons of why is not taken seriously by the ISX and listed companies. This study is conducted on Iraqi Stock Exchange with taking samples from each sectors of the Iraqi Stock Exchange. Secondary and primary data have been used in this study in order to collect quality information. The research has used a combination of questionnaire and interview to get an in-depth understanding of the study area. The theoretical sides of a serious Corporate Governance or its codes have been discussed by providing a frame work of Corporate Governance in Iraq and the authorities that have influence on listed companies by their regulations, laws and standards. Also, practical side of a serious Corporate Governance has been identified by analyzing the data. The results of this study showed that, Corporate Governance is taken serious in the Bank sector of the Iraqi Stock Exchange and is not taken serious in other sectors such as Insurance, Agricultural and Tourism. However, these results are based on the current available data and investigating, which leads the Iraqi Stock Exchange and companies to be questioned about their authentication.